Pengaruh Faktor – Faktor Fundamental Keuangan Terhadap Harga Saham Pada Industri Keuangan Sub Sektor Perbankan Bursa Efek Indonesia Tahun 2019 - 2020 - Putri, Wulan Wahyuni Rossa; Tartilla, Nilda (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Shares are considered to be an indicator of success in managing a banking company because share prices that have increased indicate that the company is in good condition. The closing price is the last price that appears on a company's shares before the stock exchange closes. The aim of this research is to find out how fundamental financial factors influence stock prices in the sub-banking financial industry of the Indonesian Stock Exchange. Secondary data from audited annual reports on the official IDX website, www.idx.co.id, served as the data source for this research. The research population consisted of financial industry companies in the banking sub-sector from 2019 to 2020. Sample selection was conducted using purposive sampling. Descriptive analytical methods with the SPSS version 25 program were employed for analysis, and hypothesis testing utilized the multiple linear regression method. The findings indicate that Price to Earnings Ratio (PER) and Earnings Per Share (EPS) have a significant influence on stock prices, whereas Return on Equity (ROE) and Net Profit Margin (NPM) do not. However, collectively, NPM, ROE, PER, and EPS as fundamental financial indicators have an impact on stock prices. Keywords: Stock Price, NPM, ROE, PER dan EPS